2003
DOI: 10.1207/s15327914nc4502_04
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Lung Cancer Risk From a 14-Year Population-Based Prospective Study in Japan: With Special Reference to Fish Consumption

Abstract: N-3 polyunsaturated fatty acids in fish oil exhibit a variety of health benefits, and there is evidence that they can inhibit the development of human lung mucoepidermoid and other carcinomas. To examine the hypothesis that fish consumption reduces the risk of lung cancer, we conducted a population-based prospective study, following 5,885 residents for 14 yr. Person-years were used to calculate the relative risk (RR) by the Cox proportional hazards model, with adjustment for potential confounding factors. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 27 publications
1
66
0
3
Order By: Relevance
“…44 All of these studies assessed lung cancer incidence relative to fish consumption. In 1 study, 6 fish consumption was associated with a reduced risk of lung cancer (RR, 0.32; 95% CI, 0.13-0.76). In another study, fish consumption was associated with an increased risk of lung cancer 46 (IRR, 3.0; 95% CI, 1.2-7.3).…”
Section: Lung Cancermentioning
confidence: 98%
“…44 All of these studies assessed lung cancer incidence relative to fish consumption. In 1 study, 6 fish consumption was associated with a reduced risk of lung cancer (RR, 0.32; 95% CI, 0.13-0.76). In another study, fish consumption was associated with an increased risk of lung cancer 46 (IRR, 3.0; 95% CI, 1.2-7.3).…”
Section: Lung Cancermentioning
confidence: 98%
“…The traditional Japanese diet, which is low in fat and high in several phytochemicals, might help decrease the risk of death due to lung cancer. (24)(25)(26)(27) Deletion-type polymorphism CYP2A6, the principal enzyme in the metabolic activation of tobacco-specific nitrosamines, was found to be inversely associated with lung cancer among Japanese male smokers. (28) It has been demonstrated that the frequency of occurrence of this variant is higher amongst Japanese than among Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…However, there isn't any reason why smokers shouldn't be acquainted with the rather compelling evidence that currently exists suggesting that fish consumption or DHA supplementation could protect them provided that it is concurrently made clear that smoking cessation will be far more protective than any counter measure that might be contemplated. In the impressive Takezaki study [12] the most substantial reduction in lung cancer risk roughly an 80% reduction relative to that of subjects eating fish rarely was noted in subjects consuming 3 or more fish meals weekly. I calculate that 4 5 ounce servings of Bluefin tuna weekly would provide an intake of long -chain omega -3 averaging out to about 1.3 g daily the majority of which would be DHA.…”
Section: Resultsmentioning
confidence: 99%
“…A prospective Japanese study followed 5,885 subjects for 14 years, during which time 51 lung cancer cases developed [12]. Baseline fish intake was stratified as less than 1 time weekly, 1 or 2 times weekly and 3 or more times weekly.…”
Section: Fish Consumption May Protect Smokers From Lung Cancermentioning
confidence: 99%